2016
DOI: 10.15390/eb.2016.6214
|View full text |Cite
|
Sign up to set email alerts
|

Turkish University Students' Perceptions towards Their Syrian Classmates

Abstract: Keywords

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
(15 reference statements)
1
9
0
1
Order By: Relevance
“…The teachers added that when the local students were told to feel empathy with the refugee students and tried to understand them and put themselves in their places, local student became more sensitive, thoughtful and helpful towards their refugee classmates. A similar finding was also observed by Ergin (2016) who also reported that the participant students had generally positive attitudes towards their classmates when they spent time together.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The teachers added that when the local students were told to feel empathy with the refugee students and tried to understand them and put themselves in their places, local student became more sensitive, thoughtful and helpful towards their refugee classmates. A similar finding was also observed by Ergin (2016) who also reported that the participant students had generally positive attitudes towards their classmates when they spent time together.…”
Section: Discussionsupporting
confidence: 85%
“…Studies reporting the current situation of the refugee students in Turkey were in surge. These studies included analysis of educational policies about refugees (Alpaydin, 2017), problems regarding educating refugees (Akkaya, 2013;Arabaci et al, 2013), teachers' practices in classrooms with refugee students (Erden, 2013;Emin, 2016); refugee students' experiences (Döner, Özkara, & Kahveci, 2013) and local students' perspectives on refugee students (Ergin, 2016). However, studies on how refugee students affected local students were limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forced displacement has been a "tragic destiny" of humanity (Ergin 2016). Even the first human beings, Adam and Eve, experienced it when they ate the "forbidden fruit", according to the Jewish, Christian and Islamic religions.…”
Section: Introductionmentioning
confidence: 99%
“…Being one of the neighboring countries, Turkey has become a destination for 3.6 million Syrians, which has made it host to the largest group of refugees (UNHCR 2020). With a welcoming open-door policy, Turkey has provided the Syrian refugees with humanitarian aid, the right to education, residence and work permits (Ergin 2016). It was recently reported that government spending on the Syrians in Turkey has already exceeded USD 40 billion (Euronews 2019).…”
Section: Introductionmentioning
confidence: 99%